Dispositional Optimism and Perceived Stress in Adolescents Following Parental Divorce - Lintang Kinasih; Christiana Hari Soetjiningsih; Emmanuel Satyo Yuwono (IJE : Interdisciplinary Journal of Education, 2026)
Parental divorce constitutes a major family transition that may heighten adolescents’ perceived stress, whereas optimism is generally regarded as a protective psychological resource. This study examined the association between dispositional optimism and perceived stress among adolescents whose parents had divorced. A quantitative, cross-sectional correlational design was employed with 64 adolescents aged 14–18 years residing in Grobogan Regency, Indonesia. Participants were recruited through convenience sampling and completed online measures described as Indonesian adaptations of the Life Orientation Test–Revised and the Perceived Stress Scale. Because both variables deviated significantly from normality, the hypothesis was tested using Spearman’s rank-order correlation. The analysis revealed a statistically significant, moderate positive association between optimism and perceived stress (rₛ = .488, p < .001; approximate 95% CI .28, .66), contrary to the hypothesized negative relationship. This finding should not be interpreted as evidence that optimism causes stress. Rather, it may reflect context-specific expectations, compensatory positive thinking elicited by distress, measurement-related characteristics, or unmeasured family and social conditions. The findings underscore the importance of distinguishing generalized dispositional optimism from family-specific hopes, including expectations of parental reconciliation. Counseling interventions should preserve adolescents’ positive future orientation while fostering realistic appraisal, emotional acceptance, flexible goal adjustment, and access to supportive relationships.